THE RELATIONSHIP BETWEEN MOVEMENT ACTIVITIES IN IMPROVING THE LEARNING OUTCOMES OF GRADE IX STUDENTS OF STATE MIDDLE SCHOOL 17 MEDAN - Samosir, Niko S.P; Damanik, Saipul Ambri (Universitas Negeri Medan, 2025)
This study aims to develop a volleyball underhand passing training model. This study was conducted at Sumbul 2 State Junior High School. The research and development used a questionnaire, a questionnaire, and a volleyball underhand passing skill test to collect quantitative and qualitative data. The model was first validated by two sports experts: a volleyball coach and a volleyball lecturer. Data analysis showed an improvement in the results of the volleyball underhand passing training in both small and large group tests. The small group test involved ten students, and the large group test involved twenty students. The validation results for the development of four variations of the volleyball underhand passing training. The results of the small group test on ten students from Sumbul 2 State Junior High School indicated that the four training forms met the criteria for feasibility and validity. The validity percentage of the questionnaire distributed to the sample showed that 86%-100% of students acknowledged that the training forms met the criteria and could be used during training. This indicates that the four variations met the criteria for feasibility.